2022
DOI: 10.1093/heapol/czac008
|View full text |Cite
|
Sign up to set email alerts
|

What makes working together work? A scoping review of the guidance on North–South research partnerships

Abstract: At their best, research partnerships provide a mechanism to optimise each partner’s strengths, make scientific discoveries and achieve development goals. Each partner stands to gain from the relationship and perceives it to be fair. However, partnerships between institutions in the global North and the global South have been beleaguered by structural inequalities and power imbalances and Northern stakeholders have been criticised for perpetuating paternalistic or neo-colonial behaviours. As part of efforts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Interviews with early to mid-career and senior researchers and research managers at four institutions in anglophone eastern and southern Africa revealed wide-ranging experiences of partnership with HIC collaborators, both positive and negative. Existing principles for partnership [28][29][30] provide good coverage of the issues that participants described as being the key determinants of a healthy partnership, for example: mutual respect, involvement of all partners from concept design stage throughout the research lifecycle, clear governance and open communication. A small number of participants referred to published partnership guidelines, but none mentioned having used them.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interviews with early to mid-career and senior researchers and research managers at four institutions in anglophone eastern and southern Africa revealed wide-ranging experiences of partnership with HIC collaborators, both positive and negative. Existing principles for partnership [28][29][30] provide good coverage of the issues that participants described as being the key determinants of a healthy partnership, for example: mutual respect, involvement of all partners from concept design stage throughout the research lifecycle, clear governance and open communication. A small number of participants referred to published partnership guidelines, but none mentioned having used them.…”
Section: Discussionmentioning
confidence: 99%
“…This was a qualitative study informed by a scoping review of the literature on principles and guidelines for ‘North–South’ research partnerships [ 28 ]. Semi-structured interviews were conducted with key informants from a sample of research institutions in anglophone eastern and southern Africa.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations